Preparation method of carbon fiber shell of unmanned aerial vehicle
By performing multiple surface modification treatments and nanofiller enhancement on the drone carbon fiber shell, combined with vacuum bag molding and hot pressing curing processes, the problems of insufficient interface bonding force and limited improvement of matrix performance are solved, and a high-strength, high toughness and long-life UAV carbon fiber shell is achieved.
Patent Information
- Application Number
- CN202510291502.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the interface bonding force of the UAV carbon fiber shell is insufficient, resulting in the interface being easily delaminated or debonded under dynamic loads, and the matrix performance is limited, and the fatigue and impact resistance are insufficient.
By performing multiple surface modification treatments on carbon fibers, including silane coupling agent plating, graphene oxide deposition and PVA modification, nano SIO2 and carbon nanotubes are introduced into the resin matrix, combining the synergistic toughening design of flexible toughening agents. The process optimization of vacuum bag molding and hot pressing curing is adopted to form a dense and non-porous material microstructure.
It significantly improves the interface bonding strength between carbon fiber and resin matrix, improves the strength and fatigue life of the composite material, enhances the overall strength and dimensional stability of the material, and solves the problems of insufficient interface bonding force and layered cracking.
Smart Images

Figure CN119795621A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a method for preparing a carbon fiber shell of an unmanned aerial vehicle. Background Art
[0002] Carbon fiber composite materials have been widely used in aerospace, automobile manufacturing, and drones due to their excellent specific strength, specific stiffness, and corrosion resistance. In particular, in the manufacture of drone shells, the demand for lightweight, high strength, and fatigue resistance is more urgent. However, drone shells need to withstand complex dynamic loads and impact conditions in actual use, and the requirements for the interface bonding strength, matrix toughness, and manufacturing process of composite materials are more stringent. To this end, the existing technology improves the overall performance of composite materials by modifying the surface of carbon fibers, adding fillers to the resin matrix to toughen or strengthen them, and optimizing the molding process. Although these technical means can improve the mechanical properties of materials to a certain extent, they still have significant shortcomings in the face of the comprehensive requirements of multiple performance indicators.
[0003] The interface treatment of existing technologies mainly relies on surface activation or single functionalization to enhance the bonding force between carbon fiber and resin matrix, but this method fails to achieve multi-scale interface enhancement, resulting in easy delamination or debonding of the interface under dynamic load; matrix modification uses toughening agents or inorganic fillers, but the independent application of the two often makes it difficult to balance strength and toughness, and the improvement of matrix performance is limited; the molding process greatly weakens the fatigue and impact resistance of composite materials due to the residual problems of bubbles and pores. In addition, the existing technology fails to achieve the coordinated optimization of interface-matrix-process, resulting in the overall performance of the material being out of touch with the actual application requirements of the drone shell, such as low fatigue life, poor impact resistance and insufficient dimensional stability. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a carbon fiber shell of an unmanned aerial vehicle, which solves the problems of insufficient interface bonding strength and delamination and cracking in the prior art.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing a carbon fiber shell of an unmanned aerial vehicle comprises the following steps: Carbon fiber surface modification: surface cleaning, activation, chemical plating and surface functionalization of carbon fiber; Resin matrix preparation: epoxy resin is mixed with a flexible toughening agent, nanofiller and curing agent, and vacuum degassing is performed; Carbon fiber laying: Lay the modified carbon fiber cloth at a set angle and sequence; Vacuum bag molding: vacuum seal the carbon fiber composite material after layering; Hot press curing: curing the composite material in an autoclave by setting the process conditions of temperature, pressure and time; Demolding and post-processing: demoulding and trimming of the cured material.
[0006] Preferably, the surface modification treatment of the carbon fiber includes: The carbon fibers were cleaned with a 2–5wt% alkaline solution for 10–30 minutes. The carbon fibers were activated using air plasma at a power of 50–100 W for 5–15 minutes. A silane coupling agent solution with a mass concentration of 0.5-1.5wt% is coated on the surface of the carbon fiber, the immersion time is 15-30 minutes, and the carbon fiber is dried at 80-100°C for 20-40 minutes.
[0007] Preferably, the step of chemically plating the carbon fiber surface comprises immersing the carbon fiber in a 0.05-0.2wt% graphene oxide dispersion, dispersing with the aid of ultrasound, the dipping time is 10-20 minutes, and drying at 90-120°C for 30-60 minutes.
[0008] Preferably, the surface functionalization modification is completed by spraying 2-5 wt% polyvinyl alcohol solution and drying at 80-100° C. for 15-30 minutes.
[0009] Preferably, the resin matrix comprises: 80–90 wt% bisphenol A epoxy resin; 10–15 wt% alicyclic amine curing agent; 5–10 wt% of a flexible toughening agent; 0.5–2wt% nano-SIO2 and 0.1–0.5wt% carbon nanotubes.
[0010] Preferably, the steps of preparing the resin matrix include: Dissolve the flexible toughening agent in the epoxy resin at 50–70°C, stirring at 500–1000 rpm for 20–40 minutes; Nano-SIO2 and carbon nanotubes were added to epoxy resin and dispersed by ultrasonic dispersion equipment at a frequency of 40–60 kHz for 30–60 min; Add the alicyclic amine curing agent to the above mixture of the flexible toughening agent and the epoxy resin, and stir at 300-500 rpm for 10-20 minutes.
[0011] Preferably, the carbon fiber ply angles include -45°, 0°, 45°, and 90°, and the number of plies is 3-10. The prepared resin matrix is poured between each layer and compacted with a roller to remove bubbles.
[0012] Preferably, in the vacuum bag forming step, the gas in the sealed mold is evacuated to -0.08 to -0.1 MPa by a vacuum pump.
[0013] Preferably, the process conditions of the autoclave curing include: Initially heat to 80–100°C and keep warm for 1–2 hours; Raise the temperature to 120–150°C and keep warm for 2–3 hours; The cooling rate was 1–3°C / min.
[0014] Preferably, the demoulding and post-processing steps include cooling the cured composite material to room temperature before demoulding, and trimming the edge of the shell by mechanical cutting equipment.
[0015] The present invention provides a method for preparing a carbon fiber shell of an unmanned aerial vehicle, which has the following beneficial effects: 1. The present invention significantly improves the interfacial bonding strength between carbon fiber and resin matrix through multiple treatments of silane coupling agent plating, graphene oxide deposition and PVA modification. Compared with the technical solution of only using a single surface activation or modification method in the prior art, it solves the problems of insufficient interfacial bonding and delamination cracking, and realizes multi-scale enhancement of high-strength interface.
[0016] 2. The present invention introduces nano-SIO2 and carbon nanotubes into the resin matrix, combined with the synergistic toughening design of the flexible toughening agent, to construct a hierarchical nano-network structure, which greatly improves the toughness and fatigue life of the composite material. In the prior art, the reinforcement means of the resin matrix are single and lack multi-scale synergy, which makes the composite material prone to microcrack expansion. The present invention overcomes this defect well.
[0017] 3. The present invention forms a dense and non-porous material microstructure through process optimization of vacuum bag forming and hot pressing curing. In the traditional process, the strength and stability of the composite material are easily affected due to uneven curing or residual pores. The process design of the present invention not only effectively eliminates internal defects, but also improves the overall strength and dimensional stability of the material.
[0018] 4. The overall design of the present invention realizes the organic combination of interface functionalization, matrix reinforcement and process optimization. Compared with the technical path of improving only one aspect in the prior art, it solves the problem of difficult balance between mechanical properties and durability of composite materials, and successfully realizes the preparation of high-strength, high-toughness and long-life carbon fiber shells for UAVs, providing comprehensive and reliable technical support for high-performance applications of UAVs. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Please see attached Figure 1 The present invention provides a method for preparing a carbon fiber shell of a drone, comprising the following steps: 1. Carbon fiber surface modification 1.1 Surface cleaning and activation Process content: Soak the carbon fiber cloth in 2–5wt% NaOH solution and stir for 10–30 minutes at room temperature to remove organic pollutants, grease, and loose particles on the surface.
[0022] After cleaning, the carbon fibers were rinsed with deionized water several times until neutral and then dried in a drying oven at 80–100 °C for 20–40 min.
[0023] The dried carbon fibers were treated by air plasma with a plasma power of 50–100 W for 5–15 min to further clean the surface and introduce polar functional groups.
[0024] Mechanism analysis: Alkaline washing removes contamination through saponification reaction with surface organic matter, while increasing the roughness of the carbon fiber surface and improving the wettability of the fiber surface.
[0025] Air plasma destroys the inert graphite structure through high-energy excitation, introduces polar functional groups such as hydroxyl (-OH) and carboxyl (-COOH) on the fiber surface, improves surface activity, and increases the chemical binding sites between the fiber and subsequent modifiers.
[0026] 1.2 Silane coupling agent plating Process content: Prepare the silane coupling agent solution: dissolve γ-aminopropyltriethoxysilane (KH550) in a mixture of ethanol and deionized water (ethanol: water = 7:3), and adjust the pH of the solution to 4–5 with glacial acetic acid.
[0027] Immerse the carbon fibers in the silane solution for 15–30 minutes.
[0028] After impregnation, take out the carbon fiber and dry it at 80-100°C for 20-40 minutes to allow the silane coupling agent to form a uniform coating on the fiber surface.
[0029] Mechanism analysis: The ethoxy group (-OEt) in the silane coupling agent molecule is hydrolyzed to generate silanol (-SiOH), which undergoes a condensation reaction with the hydroxyl group on the surface of the carbon fiber to form a stable silicon-oxygen bond (Si–O–C).
[0030] The amino group (-NH2) at the other end of the silane molecule undergoes a cross-linking reaction with the epoxy group of the epoxy resin, further enhancing the chemical bonding between the carbon fiber and the matrix.
[0031] 1.3 Graphene oxide deposition Process content: Preparation of graphene oxide (GO) dispersion: Graphene oxide powder (0.05–0.2 wt%) was added to deionized water and treated with an ultrasonic dispersion device at a frequency of 40–60 kHz for 10–20 min to ensure that GO was fully and evenly dispersed.
[0032] After carbon fiber coating, it was immersed in graphene oxide dispersion for 10–20 min.
[0033] The fibers were then dried at 90–120 °C for 30–60 min to form a uniform GO deposition layer.
[0034] Mechanism analysis: The surface of graphene oxide is rich in polar functional groups such as hydroxyl (-OH) and carboxyl (-COOH), which can react chemically with the functional groups of the silane coating to further enhance the bonding strength of the interface.
[0035] As a two-dimensional nanomaterial, GO can form a multi-scale reinforcement layer on the fiber surface, effectively dispersing the interfacial stress through physical barrier effect, preventing crack propagation, and providing conductivity and thermal stability.
[0036] 1.4 Surface functionalization Process content: Prepare polyvinyl alcohol (PVA) solution: dissolve 2–5 wt% PVA in deionized water and heat to 90 °C with stirring until completely dissolved.
[0037] Use a spraying device to evenly spray the PVA solution onto the surface of the carbon fiber on which graphene oxide is deposited, with a spraying amount of 20–50 mL / m².
[0038] After spraying, dry the carbon fiber cloth at 80–100°C for 15–30 minutes.
[0039] Mechanism analysis: The hydroxyl groups (-OH) in PVA physically or chemically interact with the epoxy resin matrix to form a dynamic hydrogen bond network. Under load or fatigue conditions, the hydrogen bonds can break and rebuild, absorbing stress and improving the fatigue performance of the composite material.
[0040] PVA can also improve the interfacial wettability and enhance the compatibility between carbon fiber and resin.
[0041] 2. Resin Matrix Preparation Material mixing and dispersion Process content: Mix epoxy resin (80–90 wt%) with 5–10 wt% toughening agent (CTBN or SEBS) and stir at 50–70 °C for 20–40 min until the toughening agent is completely dissolved.
[0042] 0.5–2wt% of nano-SIO2 and 0.1–0.5wt% of carbon nanotubes (CNTs) were added, and the fillers were uniformly dispersed using an ultrasonic dispersion device (frequency 40–60kHz, time 30–60 minutes).
[0043] Finally, add 10–15 wt% of alicyclic amine curing agent (such as IPDA) and stir at 300–500 rpm for 10–20 minutes until uniform.
[0044] Mechanism analysis: CTBN reacts chemically with the epoxy group of epoxy resin through its carboxyl group (-COOH) to form flexible chain segments in the matrix, effectively improving the toughness of the resin.
[0045] Nano-SSIO2 and CNTs form a three-dimensional nano-network structure through physical reinforcement and chemical cross-linking, which improves the modulus and interface bonding strength of the matrix.
[0046] Vacuum degassing Process content: The mixed resin matrix is placed under vacuum conditions (-0.09 to -0.1MPa) for degassing for 10-20 minutes to remove bubbles introduced during the mixing process.
[0047] Mechanism analysis: The presence of bubbles will lead to pore defects inside the material. These bubbles can be eliminated by vacuum degassing to improve the uniformity and mechanical properties of the material.
[0048] 3. Carbon fiber laying and molding Laying and pouring Process content: The modified carbon fiber is laid alternately at ±45° and 0° / 90°. After each layer of carbon fiber cloth is laid, a layer of prepared resin matrix is poured and compacted with a roller.
[0049] Mechanism analysis: Multi-directional lamination enhances the multi-directional load-bearing capacity of composite materials, and roller compaction reduces bubbles and interface defects.
[0050] Vacuum bag forming Process content: Cover the laminated composite material with a vacuum bag and evacuate the internal air to -0.08 to -0.1MPa.
[0051] Mechanism analysis: Vacuum forming compacts the layers of the composite material through external pressure to eliminate micropores in the material.
[0052] Hot press curing Process content: Initially heat to 80–100°C and keep warm for 1–2 hours; Raise the temperature to 120–150°C and keep warm for 2–3 hours; Cool down to room temperature at a cooling rate of 1–3 °C / min.
[0053] Mechanism analysis: The autoclave provides a uniform temperature and pressure environment to ensure that the resin is fully cross-linked and cured, thereby improving the material's density and mechanical properties.
[0054] Demolding and post-processing Process content: demoulding after cooling and trimming the edges with mechanical equipment. Example
[0055] Carbon fiber surface modification Soak the carbon fiber cloth in 3wt% NaOH solution and stir gently for 20 minutes at room temperature. Rinse with deionized water three times until the solution is neutral. Dry at 90℃ for 30 minutes.
[0056] The dried carbon fiber is placed in a plasma treatment device with a power of 80W and an activation time of 10 minutes.
[0057] Prepare a silane coupling agent solution by dissolving 1wt% KH550 in a mixture of ethanol and water (ethanol: water = 7:3) and adjusting the pH to 4.5. Immerse the carbon fiber in the solution for 25 minutes. Then take out the carbon fiber and dry it at 90°C for 30 minutes.
[0058] Prepare a graphene oxide dispersion with a concentration of 0.1wt%. Ultrasonic treatment time is 15 minutes at a frequency of 50kHz. Immerse the treated carbon fiber cloth in the dispersion for 15 minutes. Then dry it at 100℃ for 40 minutes.
[0059] Resin matrix preparation 85 wt% of epoxy resin and 7 wt% of CTBN toughening agent were mixed and stirred at 60 °C for 30 minutes.
[0060] 1.5 wt% of nano-SIO2 and 0.2 wt% of carbon nanotubes were added, and stirring was continued for 10 minutes. The ultrasonic treatment time was 40 minutes, and the frequency was 55 kHz.
[0061] Add alicyclic amine curing agent with a mass fraction of 12wt%, stir at a speed of 400rpm for 15 minutes.
[0062] Molding and curing Lay 5 layers of carbon fiber cloth in the order of ±45°, 0° / 90°, apply a layer of prepared resin after each layer is laid, and use a roller to compact evenly.
[0063] Vacuum bag molding is used, and the vacuum degree is controlled at -0.09MPa. Put it into the autoclave, the initial curing temperature is 90℃, and the heat preservation time is 1.5 hours. Then the temperature is raised to 130℃ and kept for 2 hours. The cooling rate is 2℃ / min until room temperature.
[0064] Finally, demould and trim the edges of the shell. Example
[0065] Carbon fiber surface modification The carbon fibers were soaked in 4 wt% NaOH solution for 15 minutes, rinsed with deionized water until pH was neutral, and dried at 100 °C for 25 minutes.
[0066] The plasma power was set to 70 W and the treatment time was 12 minutes.
[0067] A 0.8 wt% KH550 coupling agent solution was used, the immersion time was 20 minutes, the drying temperature was 85°C, and the drying time was 35 minutes.
[0068] The concentration of graphene oxide solution was 0.15wt%, the ultrasonic frequency was 45kHz, the treatment time was 12 minutes, the dipping time was 12 minutes, and the drying temperature was 110°C for 30 minutes.
[0069] The concentration of PVA solution is 3wt%. The spraying amount is 30mL / m², the drying temperature is 95℃, and the drying time is 20 minutes.
[0070] Resin matrix preparation The mass ratio of epoxy resin to SEBS toughening agent was 90:10, and the mixture was stirred at 65°C for 40 minutes.
[0071] The addition amount of nano-SIO2 is 1wt%, and that of carbon nanotubes is 0.3wt%. The ultrasonic frequency is 60kHz, and the dispersion time is 30 minutes.
[0072] The curing agent addition ratio was 10 wt %, the stirring speed was 500 rpm, and the stirring time was 10 minutes.
[0073] Molding and curing Lay 8 layers of carbon fiber cloth alternately at 0° / 90°, apply resin at 45% of the mass of the carbon fiber, and compact evenly with a roller.
[0074] Vacuum bag molding, vacuum degree is -0.08MPa. The initial curing temperature is 100℃, the time is 1 hour; then the temperature is raised to 150℃, the heat preservation time is 2 hours. The cooling rate is 1.5℃ / min.
[0075] After demoulding, the edges are trimmed using cutting equipment to complete the shell preparation. Example
[0076] Carbon fiber surface modification The carbon fiber cloth was soaked in 2.5wt% NaOH solution for 30 minutes. After cleaning, it was rinsed with deionized water until neutral. The drying temperature was 80℃ and the drying time was 40 minutes.
[0077] The plasma power was 100 W and the treatment time was 8 minutes.
[0078] Use 1wt% KH550 solution, soak for 30 minutes, dry at 100℃, and dry for 20 minutes.
[0079] The concentration of graphene oxide dispersion was 0.05wt%, the ultrasonic frequency was 50kHz, the time was 20 minutes, the dipping time was 20 minutes, and the drying temperature was 120°C for 50 minutes.
[0080] Use 4wt% PVA solution, spraying amount is 25mL / m², drying temperature is 90℃, drying time is 25 minutes.
[0081] Resin matrix preparation The epoxy resin accounts for 88wt%, the CTBN toughening agent accounts for 8wt%, the stirring temperature is 55℃, and the stirring time is 35 minutes.
[0082] The mass ratio of nano-SIO2 to carbon nanotubes was 8:1, and the total filler ratio was 2wt%. The ultrasonic frequency was 58kHz, and the time was 35 minutes.
[0083] The curing agent is alicyclic amine with a mass fraction of 10wt%. The stirring speed is 400rpm and the stirring time is 12 minutes.
[0084] Molding and curing Lay 6 layers of carbon fiber cloth in the order of ±45°. After pouring the resin on each layer, use a scraper to evenly apply and compact it.
[0085] After the vacuum bag is sealed, the vacuum degree is -0.1MPa. The curing conditions are: initial temperature 80℃, keep warm for 1.5 hours; heat up to 135℃, keep warm for 2.5 hours. The cooling rate is 3℃ / min.
[0086] After demoulding, the edges are trimmed and the thickness and size are tested to ensure that the finished product meets the design requirements. Example
[0087] Carbon fiber surface modification The carbon fibers were treated with 3.5 wt% NaOH solution for 25 minutes, rinsed to neutrality, and dried at 95 °C for 30 minutes.
[0088] The surface was treated with 90 W plasma for 10 minutes to increase the surface polarity.
[0089] The concentration of silane coupling agent is 1.2wt%, the immersion time is 25 minutes, the drying temperature is 90°C, and the drying time is 35 minutes.
[0090] The graphene oxide concentration was 0.2 wt %. The ultrasonic frequency was 60 kHz, the time was 15 minutes, the dipping time was 15 minutes, and the drying temperature was 110° C., the time was 40 minutes.
[0091] The PVA solution is 2wt%, the spraying amount is 35mL / m², the drying temperature is 85℃, and the drying time is 30 minutes.
[0092] Resin matrix preparation The epoxy resin accounts for 86wt%, the toughening agent is CTBN, accounting for 9wt%, the stirring temperature is 60℃, and the stirring time is 40 minutes.
[0093] The amount of nano-SIO2 is 1.2wt%, the amount of carbon nanotubes is 0.25wt%, the ultrasonic frequency is 55kHz, and the time is 45 minutes.
[0094] The curing agent is alicyclic amine, the addition ratio is 12wt%, the stirring speed is 450rpm, and the time is 15 minutes.
[0095] Molding and curing Lay 6 layers of carbon fiber cloth alternately at 0° / 90°, apply resin on each layer, and lay the next layer after compacting.
[0096] The vacuum degree was controlled at -0.09 MPa, the initial curing temperature was 85°C, and the holding time was 2 hours. The temperature was raised to 140°C, and the holding time was 3 hours. The cooling rate was 2°C / min.
[0097] After demoulding, the surface is cut and trimmed to be flat and smooth, and the size meets the design specifications.
[0098] Comparative Example 1 (Compared with Example 1, graphene oxide deposition was omitted) Carbon fiber surface modification The carbon fiber cloth was washed with 3wt% NaOH solution for 20 minutes, rinsed with deionized water three times until neutral, and dried at 90°C for 30 minutes.
[0099] Plasma activation treatment, power 80W, time 10 minutes.
[0100] Prepare 1wt% silane coupling agent KH550 solution and soak the carbon fiber cloth for 25 minutes. Dry at 90℃ for 30 minutes.
[0101] The difference from Example 1 is that the graphene oxide deposition step is eliminated, and the carbon fiber cloth modified with the silane coupling agent is directly used for subsequent molding.
[0102] Resin matrix preparation The formula and process are exactly the same as those in Example 1.
[0103] Molding and curing Lay 5 layers of carbon fiber cloth in the order of ±45°, 0° / 90°, apply resin and compact.
[0104] Vacuum bag molding, vacuum degree is -0.09MPa, curing temperature is 90℃, time is 1.5 hours; heating to 130℃, time is 2 hours. Cooling rate is 2℃ / min.
[0105] Demolding and finishing are the same as in Example 1.
[0106] Comparative Example 2 (Compared with Example 2, PVA modification was cancelled) Carbon fiber surface modification The carbon fiber cloth was treated with 4 wt% NaOH solution for 15 minutes, washed with deionized water, and dried at 100 °C for 25 minutes.
[0107] The plasma power was set to 70 W and the treatment time was 12 minutes.
[0108] The concentration of silane coupling agent was 0.8wt%, the immersion time was 20 minutes, the drying temperature was 85°C, and the drying time was 35 minutes.
[0109] Deposition was performed using a 0.15 wt % graphene oxide dispersion, with a dipping time of 12 min and a drying temperature of 110 ° C for 30 min.
[0110] Difference from Example 2: The PVA solution spraying modification step is eliminated.
[0111] Resin matrix preparation The formula and process are exactly the same as those in Example 2.
[0112] Molding and curing Lay 8 layers of carbon fiber cloth alternately at 0° / 90°, and apply and compact the resin at 45% of the mass of the carbon fiber.
[0113] Vacuum bag molding, vacuum degree is -0.08MPa. Curing temperature is 100℃, time is 1 hour; heating to 150℃, time is 2 hours. Cooling rate is 1.5℃ / min.
[0114] Demolding and finishing are the same as in Example 2.
[0115] Comparative Example 3 (Compared with Example 3, the resin fillers of nano-SIO2 and CNTs were removed) Carbon fiber surface modification Completely consistent with Example 3.
[0116] Resin matrix preparation The epoxy resin accounts for 88wt%, and the CTBN toughening agent accounts for 8wt%. Stirring is carried out at 55℃ for 35 minutes.
[0117] Without adding nano-SIO2 and carbon nanotubes, 10 wt% of alicyclic amine curing agent was directly added, and the stirring speed was 400 rpm for 12 minutes.
[0118] The difference from Example 3: No nano-SIO2 and carbon nanotube fillers are added to the resin matrix.
[0119] Molding and curing Lay 6 layers of carbon fiber cloth at ±45°. After pouring the resin on each layer, apply it evenly with a scraper and compact it.
[0120] The vacuum bag was sealed with a vacuum degree of -0.1 MPa. The curing temperature was 80°C for 1.5 hours; the temperature was raised to 135°C for 2.5 hours. The cooling rate was 3°C / min.
[0121] Demolding and finishing are the same as in Example 3.
[0122] Comparative Example 4 (Compared with Example 4, the vacuum bag forming process was eliminated) Carbon fiber surface modification Completely consistent with Example 4.
[0123] Resin matrix preparation Completely consistent with Example 4.
[0124] Molding and curing Lay 6 layers of carbon fiber cloth alternately at 0° / 90°, and compact each layer evenly with a scraper after applying resin.
[0125] The vacuum bag forming process was not used, and the laid composite material was directly placed in the autoclave.
[0126] The curing temperature is 85°C for 2 hours, and the temperature is raised to 140°C for 3 hours. The cooling rate is 2°C / min.
[0127] Demolding and finishing are the same as in Example 4.
[0128] The difference from Example 4 is that the vacuum bag sealing treatment is not performed and the hot pressing curing is performed directly.
[0129] Comparative Example 5 (Compared with Example 1, the silane coupling agent plating step is omitted) Carbon fiber surface modification The carbon fibers were treated with 3 wt% NaOH solution for 20 minutes, rinsed with deionized water until neutral, and dried at 90 °C for 30 minutes.
[0130] The plasma treatment power was 80 W and the treatment time was 10 minutes.
[0131] Directly carry out impregnation with graphene oxide dispersion with a concentration of 0.1wt%, an immersion time of 15 minutes, a drying temperature of 100°C, and a drying time of 40 minutes.
[0132] The difference from Example 1: the silane coupling agent plating step is eliminated, and only the graphene oxide treatment is performed.
[0133] Resin matrix preparation The formula and process are exactly the same as those in Example 1.
[0134] Molding and curing The molding and curing are completely consistent with those in Example 1.
[0135] Comparative Example 6 (Compared with Example 2, the toughening agent was omitted) Carbon fiber surface modification Completely consistent with Example 2.
[0136] Resin matrix preparation The epoxy resin accounts for 95wt%, the alicyclic amine curing agent accounts for 5wt%, the stirring temperature is 55℃, and the stirring time is 20 minutes.
[0137] Difference from Example 2: No flexible toughening agent CTBN or SEBS is added to the resin matrix.
[0138] Molding and curing The molding and curing are completely consistent with those of Example 2.
[0139] Experiment 1: Interface shear strength test Experimental Description Purpose The effects of different modification methods on the interface bonding performance between carbon fiber and resin matrix were verified, and the interface bonding effects of various embodiments and comparative examples were evaluated through interface shear strength tests.
[0140] Experimental procedures Sample preparation Composite material plates were prepared according to the processes of Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, and Comparative Example 5.
[0141] The composite material sheet was cut into test samples of 25 mm × 10 mm × 2 mm, ensuring that the surface was smooth and free of cracks.
[0142] Equipment preparation A microcomputer-controlled electronic universal testing machine was used, and the loading fixture used the ASTMD2344 standard short beam shear test fixture. After the equipment was calibrated, the loading speed was adjusted to 1 mm / min.
[0143] Testing Process Secure the test sample in the fixture, ensuring that the sample is in the correct position.
[0144] Start loading and record the maximum load until the sample fails.
[0145] The interfacial shear strength (unit: MPa) is calculated according to the following formula:
[0146] in: : interface shear strength; : Maximum load when the sample fails; : Shear area (sample width × thickness).
[0147] Repeat the test Each sample was tested 5 times and the average value was taken as the final data.
[0148] Experimental data Table Name:
[0149] Through the observation and analysis of the experimental data, the interface shear strength difference between the embodiment and the comparative example is significant. This difference can be attributed to the effect of the multi-level interface modification treatment in terms of mechanism. In Example 1, the reinforcing layer formed by graphene oxide on the surface of carbon fiber brings higher interface bonding force. The two-dimensional structure of graphene oxide can evenly disperse stress, and its surface functional groups and resin matrix produce chemical reactions, which effectively improves the stress transfer ability at the interface. However, in Comparative Example 1, due to the lack of graphene oxide deposition, the interface bonding force is significantly limited, showing a lower shear strength.
[0150] The shear strength of Example 2 is higher because of the introduction of the PVA modified layer. PVA provides an adaptive stress absorption mechanism through a dynamic hydrogen bond network, which makes the interface stable under high stress. This hydrogen bond network can rebuild and dynamically adjust the interface structure, thereby maintaining a high shear strength under fatigue load. In Comparative Example 2, the lack of PVA modification makes the interface's fatigue resistance insufficient and the interface strength is significantly reduced. This phenomenon shows that PVA not only improves wettability, but also optimizes the physical and chemical interactions between the fiber and the resin matrix.
[0151] The performance of Example 3 is even better, mainly due to the chemical plating of the silane coupling agent. During the silane treatment process, the formation of hydroxyl groups and silicon oxygen bonds on the fiber surface significantly improves the chemical bonding strength of the interface and enhances the interface polarity. This effect is particularly obvious under high load conditions, which is manifested as a further improvement in shear strength. However, due to the lack of silane coupling agent plating in Comparative Example 5, the fiber surface lacks sufficient active sites, and the bonding force between the resin matrix and the fiber is significantly weakened, resulting in a significant lack of interface strength.
[0152] These experimental results show that the multilayer interface functionalization treatment technology of the present invention is effective in improving the bonding performance between carbon fiber and resin matrix. The multiple effects of graphene oxide, PVA modification and silane coupling agent form a synergistic enhancement effect, which effectively improves the interface performance of the composite material. By giving full play to the unique role of different modification methods, the problem of insufficient interface bonding strength of traditional composite materials is solved, providing a more reliable performance guarantee for the practical application of drone shells.
[0153] Experiment 2: Bending strength test Experimental Description Purpose The effects of different fillers and toughening agents on the flexural strength of the composite materials were verified, and the differences in mechanical properties of the materials in the examples and comparative examples were investigated.
[0154] Experimental procedures Sample preparation Composite material plates were prepared according to the processes of Example 1, Example 2, Example 3, Example 4, and Comparative Example 3 and Comparative Example 6.
[0155] Cut the sheet into strip samples of 100mm×10mm×2mm, ensuring that the edges of the samples are smooth and free of burrs.
[0156] Equipment preparation A microcomputer-controlled electronic universal testing machine was used, equipped with a three-point bending fixture, the clamp distance was set to 80 mm, and the load sensor range was 500N.
[0157] After the test equipment is calibrated, the loading speed is adjusted to 1 mm / min.
[0158] Testing Process Place the sample in a three-point bending fixture, making sure the force point is in the center of the sample.
[0159] Start loading and record the maximum load when the sample breaks or undergoes obvious plastic deformation .
[0160] Calculate the flexural strength (unit: MPa) according to the following formula:
[0161] in: : Maximum load (unit: N); : The distance between the supporting fixtures (unit: mm); : Sample width (unit: mm); : Sample thickness (unit: mm).
[0162] Repeat the test Each material sample was tested 5 times and the average value was calculated as the final result.
[0163] Experimental data Table Name:
[0164] Experimental data show that the bending strength of the material in the embodiment is significantly better than that in the comparative example, showing higher bending resistance and mechanical stability. The bending strength of Example 3 and Example 4 is significantly improved, which is mainly due to the synergistic effect of nano-SiO2 and carbon nanotube fillers. In the three-dimensional network formed by the distribution of fillers, carbon nanotubes provide a high modulus rigidity enhancement effect, while nano-SiO2 further improves the mechanical properties of the resin through physical reinforcement between particles and chemical cross-linking of the matrix. However, no filler is added in Comparative Example 3, and the matrix part of the composite material is more likely to have crack initiation and expansion at the stress point, resulting in low bending strength.
[0165] In contrast, the comparison between Example 2 and Comparative Example 6 reflects the key role of the toughening agent in improving the toughness and strength balance. Example 2 uses the flexible toughening agent CTBN, which forms a flexible segment with the epoxy matrix, enabling the material to disperse stress under bending load and delay crack propagation. Comparative Example 6 does not introduce a toughening agent, and the material is more prone to brittle fracture when subjected to stress, and the strength performance is poor. This shows that the introduction of a toughening agent is indispensable for improving mechanical properties.
[0166] The difference between Example 1 and Comparative Example 3 further reveals the role of surface modification in interface strength. The carbon fiber surface after graphene oxide deposition treatment forms a stronger chemical bond with the resin matrix, and the two-dimensional GO layer provides a good stress transfer path at the interface. This modification significantly improves the bearing capacity of the interface and enhances the overall bending strength. However, in Comparative Example 3, the interface bonding force is insufficient, and the carbon fiber cannot effectively transfer stress under the bending load, resulting in a more rapid failure mode.
[0167] Overall, the present invention achieves the coordinated optimization of interface bonding performance and matrix toughness and strength through a variety of strengthening means. This not only solves the problem of insufficient interface bonding and difficulty in balancing matrix strength and toughness in the prior art, but also provides a reliable mechanical basis for the high-performance application of composite materials.
[0168] Experiment 3: Fatigue life test Experimental Description Purpose By testing the fatigue life of composite materials under cyclic loading, the effects of different interface modification methods and matrix fillers on fatigue performance are verified.
[0169] Experimental procedures Sample preparation According to the processes of Example 2, Example 3 and Comparative Example 2, Comparative Example 3, composite material fatigue test samples of 50 mm×5 mm×2 mm were prepared respectively.
[0170] Check the surface quality of the sample to ensure there are no obvious defects such as cracks, dents, etc.
[0171] Equipment preparation Using electromagnetic fatigue testing machine, the test loading waveform is sine wave, load ratio (ie the minimum load is 10% of the maximum load).
[0172] The frequency was set to 10 Hz and the maximum load was set to 60% of the sample's flexural strength.
[0173] Testing Process Fix the sample in the fixture of the fatigue testing machine, ensuring that the loading direction is parallel to the sample axis.
[0174] Start the testing machine and record the fatigue life of the sample under cyclic loading (i.e. the number of cycles before fracture).
[0175] Each sample was tested 3 times and the average value was recorded as the final result.
[0176] Data recording and analysis The fatigue life data of each sample was collected, the performance differences between the embodiments and the comparative examples were analyzed, and the reasons for the performance improvement were further explained in combination with the mechanism.
[0177] Experimental data Table Name:
[0178] The experimental results show that the fatigue life of the embodiments is significantly higher than that of the comparative examples, especially Example 3, which shows a higher number of cycles. This difference mainly comes from the enhancement of the matrix performance by the nanofiller. In Example 3, nano-SiO2 and carbon nanotube fillers form a three-dimensional reinforcement network. This network structure effectively hinders the initiation and expansion of fatigue cracks, while dispersing stress concentration, thereby extending the fatigue life of the material. In Comparative Example 3, due to the lack of this nanonetwork, the matrix is more likely to fail under cyclic loads, which is manifested as a lower number of fatigue cycles.
[0179] On the other hand, the PVA modified layer introduced in Example 2 also plays an important role in improving fatigue life. The PVA dynamic hydrogen bond network provides an adaptive stress absorption mechanism at the interface, which can delay the generation and expansion of interface microcracks under cyclic load. In contrast, there is no such hydrogen bond network in Comparative Example 2, and the interface fatigue resistance is significantly reduced. Especially under high-load cyclic conditions, interfaces lacking dynamic adjustment capabilities are more prone to failure, thereby greatly shortening fatigue life.
[0180] It is worth noting that Example 3 shows a higher fatigue life than Example 2, which shows that although PVA modification contributes greatly to the fatigue performance of the interface, the filler reinforcement effect of the matrix is more comprehensive. The filler not only improves the rigidity and strength of the matrix, but also provides a more uniform path for stress transfer at the interface. This synergistic effect makes the comprehensive performance of Example 3 better than other samples. In contrast, the defects in the comparative examples expose the defects of insufficient interface bonding and difficult balance of matrix toughness in the prior art.
[0181] Overall, the experiment verified the significant improvement of fatigue performance of the present invention. Through the coordinated optimization of interface dynamic adjustment and matrix reinforcement, the technical problem of composite materials being prone to failure under cyclic loads has been completely solved. This improvement fully guarantees the long life of the UAV shell.
[0182] Experiment 4: Impact performance test Experimental Description Purpose Evaluate the impact resistance of composite materials and verify the effect of multi-layer interface functionalization and vacuum bag forming process on improving impact strength.
[0183] Experimental procedures Sample preparation According to the processes of Example 1, Example 4 and Comparative Example 1, Comparative Example 4, composite material impact test samples with a size of 80 mm×10 mm×2 mm were prepared respectively.
[0184] Check the edges of the sample to make sure they are flat and have no obvious cracks or defects.
[0185] Equipment preparation A simply supported beam impact tester was used, the initial energy of the impact hammer was set to 50 J, and the energy absorbed during the impact was recorded.
[0186] Testing Process Fix the sample on the simply supported beam fixture of the testing machine, ensuring that the sample spans across two fulcrums and the force-bearing surface is perpendicular to the fixture plane.
[0187] Adjust the height of the impact hammer to the specified position so that it hits the sample in a free-falling motion after being released.
[0188] Record the energy absorbed by the sample after impact (unit: J). If the sample breaks, record the energy absorption value; if it does not break, record the total energy absorption value.
[0189] Repeat the test Repeat the test 5 times for each sample and record the average absorbed energy to ensure that the samples are subjected to the same stress conditions during the test.
[0190] Experimental data Table Name:
[0191] The experimental results clearly show the superiority of the example materials in impact performance, especially the absorbed energy of Example 4 is significantly higher than that of other samples. The reason is that the multi-layer interface functionalization treatment makes the structure of the composite material more stable. In Example 1, the two-dimensional nanostructure of graphene oxide forms a multi-scale reinforcement layer at the interface. This structure not only improves the interface bonding strength, but also effectively delays the expansion of cracks by dispersing the impact energy. In Comparative Example 1, the lack of interface functionalization of graphene oxide leads to low stress transfer efficiency between the fiber and the resin, and the material is more prone to local failure after impact.
[0192] The vacuum bagging process is particularly critical in Example 4, which ensures high density inside the composite material and reduces the generation of defects such as bubbles or pores. Compared with the material in Comparative Example 4 that does not use vacuum bagging, the material in Example 4 shows higher absorption energy and better impact resistance. This shows that the presence of internal pores not only affects the mechanical properties, but also interferes with the transfer of impact energy, thereby causing the overall performance of the material to deteriorate. The uniform pressure provided by vacuum bagging optimizes the material microstructure during the curing process, making its energy absorption and release more uniform.
[0193] Example 4 further demonstrates the effect of technical optimization compared to Example 1. The PVA modified layer constructs a dynamic hydrogen bond network at the interface, which can effectively absorb part of the energy at the moment of impact load, and provides adaptive capabilities through the process of dynamic fracture and recombination. This flexibility enhancement mechanism is not reflected in other comparative examples, which is manifested as a significant improvement in impact performance. The shortcomings of Comparative Examples 1 and 4 further expose the defects of low interface bonding and many internal defects in traditional processes, which directly lead to the shortcomings of the material's impact resistance.
[0194] In general, the present invention synergistically improves the impact performance of composite materials through interface modification and optimization of molding process. From microstructure to macro performance, the material exhibits excellent energy absorption capacity and impact toughness, providing reliable technical support for high dynamic load scenarios such as drone shells.
[0195] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a carbon fiber shell of an unmanned aerial vehicle, characterized in that: The following steps are involved: Carbon fiber surface modification: surface cleaning, activation, chemical plating and surface functionalization of carbon fiber; Resin matrix preparation: epoxy resin is mixed with a flexible toughening agent, nanofiller and curing agent, and vacuum degassing is performed; Carbon fiber laying: Lay the modified carbon fiber cloth at a set angle and sequence; Vacuum bag molding: vacuum seal the carbon fiber composite material after layering; Hot press curing: curing the composite material in an autoclave by setting the process conditions of temperature, pressure and time; Demolding and post-processing: demoulding and trimming of the cured material.
2. The method for preparing a carbon fiber shell of an unmanned aerial vehicle according to claim 1, characterized in that: The surface modification treatment of the carbon fiber includes: The carbon fibers were cleaned with a 2–5wt% alkaline solution for 10–30 minutes. The carbon fibers were activated using air plasma at a power of 50–100 W for 5–15 minutes. A silane coupling agent solution with a mass concentration of 0.5-1.5wt% is coated on the surface of the carbon fiber, the immersion time is 15-30 minutes, and the carbon fiber is dried at 80-100°C for 20-40 minutes.
3. The method for preparing a carbon fiber shell of an unmanned aerial vehicle according to claim 1, characterized in that: The carbon fiber surface chemical plating step comprises immersing the carbon fiber in a 0.05-0.2wt% graphene oxide dispersion, dispersing with the aid of ultrasonic wave, the immersion time is 10-20 minutes, and drying at 90-120° C. for 30-60 minutes.
4. The method for preparing a carbon fiber shell of an unmanned aerial vehicle according to claim 3, characterized in that: The surface functionalization modification is completed by spraying 2-5 wt% polyvinyl alcohol solution and drying at 80-100° C. for 15-30 minutes.
5. The method for preparing a carbon fiber shell of an unmanned aerial vehicle according to claim 1, characterized in that: The resin matrix comprises: 80–90 wt% bisphenol A epoxy resin; 10–15 wt% alicyclic amine curing agent; 5–10 wt% of a flexible toughening agent; 0.5–2wt% nano-SIO2 and 0.1–0.5wt% carbon nanotubes.
6. The method for preparing a carbon fiber shell of an unmanned aerial vehicle according to claim 5, characterized in that: The preparation steps of the resin matrix include: Dissolve the flexible toughening agent in the epoxy resin at 50–70°C, stirring at 500–1000 rpm for 20–40 minutes; Nano-SIO2 and carbon nanotubes were added to epoxy resin and dispersed by ultrasonic dispersion equipment at a frequency of 40–60 kHz for 30–60 min; Add the alicyclic amine curing agent to the above mixture of the flexible toughening agent and the epoxy resin, and stir at 300-500 rpm for 10-20 minutes.
7. The method for preparing a carbon fiber shell of an unmanned aerial vehicle according to claim 6, characterized in that: The carbon fiber ply angles include -45°, 0°, 45°, and 90°, and the number of plies is 3-10. The prepared resin matrix is poured between each layer and compacted with a roller to remove bubbles.
8. The method for preparing a carbon fiber shell of an unmanned aerial vehicle according to claim 6, characterized in that: The vacuum bag forming step uses a vacuum pump to evacuate the gas in the sealed mold to -0.08 to -0.1 MPa.
9. The method for preparing a carbon fiber shell of an unmanned aerial vehicle according to claim 1, characterized in that: The process conditions of the autoclave curing include: Initially heat to 80–100°C and keep warm for 1–2 hours; Raise the temperature to 120–150°C and keep warm for 2–3 hours; The cooling rate was 1–3°C / min.
10. The method for preparing a carbon fiber shell of a drone according to claim 1, characterized in that: The demoulding and post-processing steps include demoulding after cooling the cured composite material to room temperature, and trimming the edge of the shell by mechanical cutting equipment.
Citation Information
Patent Citations
Preparation method of continuous fiber reinforced hybrid multi-scale composite material
CN104558644A
Preparation method of double sizing agent modified carbon fiber reinforced epoxy resin based composite
CN107629224A
Surface modified fibre for filling reinforcement, preparation method of surface modified fibre for filling reinforcement, and fibre reinforced composite material
CN110983775A
Modified epoxy resin composite material for ship-borne display and control console as well as preparation method and application of modified epoxy resin composite material
CN116355182A
Method of manufacturing carbon fiber-polymer resin composite
KR101952932B1
Cited By
Impact-resistant fiber-reinforced composite board as well as preparation process and application thereof
CN120096186A
Continuous fiber reinforced composite material for stent-free inflatable gas film and preparation method of continuous fiber reinforced composite material
CN120209366A
Modified carbon fiber material for unmanned aerial vehicle and processing technology of modified carbon fiber material
CN120505794A
Improvement method for rib R area wrinkle defect
CN121246288A
Method for improving rib r zone wrinkle defects
CN121246288B